Pengaruh Harga Diri Terhadap Perilaku Asertif Mahasiswa Manggarai Yang Kuliah Di Yogyakarta - Alfani, Angelina Dervila; Setyandari, Anastasia (SOLUTION, 2023)
This study aims to 1) describe the self-esteem level of Manggarai students studying in Yogyakarta; 2) describe the level of assertive behavior of Manggarai students studying in Yogyakarta; 3) Analyze the effect of self-esteem on assertive behavior in Manggarai students studying in Yogyakarta.This type of research uses quantitative. The research subjects were 40 students from Manggarai, East Nusa Tenggara who studied in Yogyakarta. This research uses Purposive Sampling Technique. Data collection used a self-esteem scale (50 valid items α=0.942) and an assertive behavior scale (41 valid items α=0.882) which were tested on 30 Manggarai students, East Nusa Tenggara who studied in Yogyakarta. Data analysis techniques using descriptive categories and simple regression analysis.The results showed that 1) 6 students (8.6%) had a very high level of self-esteem, 16 students (22.9%) had a high level of self-esteem, 18 students (25.7%) had a moderate level of self-esteem, 28 students (40%) have low self-esteem, 2 students (2.9%) have low self-esteem; 2) 4 students (5.7%) had a very high level of assertive behavior, 5 students (7.1%) had a high level of assertive behavior, 29 students (41.4%) had moderate assertive behavior, 31 students (44.3 %) %) had low assertive behavior, and 9 students (22.5%) had very low assertive behavior; 3) there is a significant influence between selfesteem on assertive behavior with a significance value of 0.000 0.05. The coefficient of determination R Square is 0.473, this means that the effect of the independent variable (self-esteem) on the dependent variable (assertive behavior) is 47.3%